2022
DOI: 10.1111/bjh.18094
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypically defined stem cell subsets in paediatric AML are highly heterogeneous and demonstrate differences in BCL‐2 expression by cytogenetic subgroups

Abstract: In adult acute myeloid leukaemia (AML), immunophenotypic differences enable discrimination of leukaemic stem cells (LSCs) from healthy haematopoietic stem cells (HSCs). However, immunophenotypic stem cell characteristics are less explored in paediatric AML. Employing a 15‐colour flow cytometry assay, we analysed the expression of eight aberrant surface markers together with BCL‐2 on CD34+CD38− bone marrow stem cells from 38 paediatric AML patients and seven non‐leukaemic, age‐matched controls. Furthermore, clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Clearly, the AML-SCs from pAML23 and pAML29 were distributed differently from all other samples, while the AML-SCs from pAML17, pAML20, and pAML21 were situated parallel to the HSCs and HPCs ( Figure 2 a). As specified in Table 1 , cytogenetic analyses of the purified AML-SCs from pAML17 and pAML21 were negative for the KMT2A rearrangement by FISH, otherwise characterizing the leukemia [ 39 ]. Interestingly, in the PCA, the AML-SCs from these two particular cases were mapped near the HSCs, whereas the AML-SCs from pAML20, pAML23, and pAML29 were separate from this healthy counterpart.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clearly, the AML-SCs from pAML23 and pAML29 were distributed differently from all other samples, while the AML-SCs from pAML17, pAML20, and pAML21 were situated parallel to the HSCs and HPCs ( Figure 2 a). As specified in Table 1 , cytogenetic analyses of the purified AML-SCs from pAML17 and pAML21 were negative for the KMT2A rearrangement by FISH, otherwise characterizing the leukemia [ 39 ]. Interestingly, in the PCA, the AML-SCs from these two particular cases were mapped near the HSCs, whereas the AML-SCs from pAML20, pAML23, and pAML29 were separate from this healthy counterpart.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical data were obtained from the AML database administered by the Nordic Society of Pediatric Oncology and Hematology (NOPHO) ( Table 1 ). Flow cytometry data from the five pediatric AML patients, and the mutational status of the AML-SC compartment in three of the patient samples were previously determined [ 39 ]. In addition, cryopreserved MNCs from five hematologically healthy pediatric patients (aged 8 to 12 years, three females and two males) were included as controls.…”
Section: Methodsmentioning
confidence: 99%
“…Chavez-Gonzalez et al demonstrated increased expression of both CD123 and CD96, but not CD117 or CD90, in putative LSCs versus normal HSCs [57]. Petersen et al likewise confirmed increased expression of CD123, as well as CLL and IL1RAP, in primitive populations from AML patients versus healthy bone marrow donors, but noted that IL1RAP, CD93, and CD25 expression was not restricted to populations harboring AML-associated genetic mutations [58]. In retrospective analyses, both CD123 and CD200 expression have demonstrated a correlation with inferior survival and other poor prognostic features (high-risk genetics, persistent MRD) [60,63].…”
Section: Immunophenotypementioning
confidence: 99%
“…Much of what has been published about pediatric AML stem cell biology borrows heavily from certain foundational tenets of adult AML stem cells, which can at times create limitations in the data. For example, many of the pediatric LSC studies base their investigation of pediatric LSCs on CD34+CD38-sorted populations of cells, which in most cases is enriching for LSCs in the context of adult AML but may miss the LSC heterogeneity that we now know is present [57][58][59][60][61][62]. With those caveats in mind, the findings from these studies could still prove to be therapeutically and prognostically interesting.…”
Section: Lsc Biology In Pediatric Myeloid Diseasementioning
confidence: 99%
“…Importantly, considerable immunophenotypic heterogeneity exists, and no single marker identifies all LSCs across AML samples [ 5 , 28 ]. For example, Petersen et al detected 50 LSC subsets showing 41 different immunophenotypic profiles within BM samples from 38 pediatric AML patients [ 29 , 30 ]. Also, the absence of an LSC marker on AML stem cells does not necessarily equal absence of disease, as shown by Bill et al demonstrating disease-related aberrancies within CLEC12A − stem cell subsets from AML cases [ 31 ].…”
Section: Introductionmentioning
confidence: 99%